'We still have bombings': school principals and insurgent violence in Southern Thailand. Issue 5 (19th October 2016) - Brooks, Melanie Carol; Sungtong, Ekkarin
Abstract : This study explored how principals in Southern Thailand lead schools in areas of violent conflict. In order to better understand principals' perspectives on working in such a context, the study was guided by Lynn Davies' Drivers of Fragility Framework, which identifies five 'drivers' of conflict in communities: (1) problems of governance; (2) lack of security; (3) weak economy; (4) cultures of power; and (5) environmental degradation. Data were collected through 30 interviews and 6 school site observations. We used Davies' Drivers of Fragility Framework as a priori analytic codes. Then, using analytic induction, we gathered additional data to identify and then refine emergent categories. Two themes emerged from the analysis of the findings, specifically the misalignment of national education policies to the local context and poor teacher quality. The findings suggested that principals were able to influence local governance, community-based security, and environmental sustainability, but were limited in their ability to influence the weak economy or cultures of power in their communities. This study is a unique contribution to research focused on how leadership is enacted in non-Western cultural contexts and sheds light on what influence principals may have in alleviating social fragility.